Analysis of the influence of tourism on nesting beaches for the Amazon turtle (Podocnemis expansa) on the Crixás-Açu river - Paiva, Lívia Schroder Memória; Leão, Tairone Paiva; Ribeiro, Paulo Lopes; Silva, Leo Caetano Fernandes da; Lara, Mariana Pastori; Navarro, Rodrigo Diana (Acta Scientiarum. Biological Sciences, 2024)
Freshwater turtles play an important ecological and social role, with Podocnemis expansa (arrau turtle) being the largest freshwater Testudine in Latin America. The overexploitation of this species for the meat and egg by-products trade has significantly reduced P. expansa populations, which makes conservation actions necessary. The reproductive success of the species is essential for its permanence, and one of the most important stages of reproduction is the nesting process. Amazon tortoises can be demanding in the selection of spawning sites, evaluating substrate, ambient temperature, vegetation, safety against predators, among other factors that affect nests. Tourism on turtle nesting beaches can be interpreted as a threat to breeding turtles, which therefore may avoid busy places, being left with limited options. With this subject in mind, this work aimed to discuss factors that interfere in the nesting process and to evaluate the possible influence of tourism on the number of spawnings of P. expansa in the Crixás-Açu river (Goiás State, Brazil), one of its natural habitats. Data were obtained on the number of nests and the presence or absence of camping/tourism on 24 beaches along the river in September and October 2020, from which a boxplot graph was produced using the R software. No correlation was found between the selection of the beaches by turtles and the presence or absence of tourism, requiring further studies on the multiple factors that influence spawning in the Crixás-Açu river. The information published here can complement the database of future studies and corroborate the knowledge necessary for the adequate protection of these animals.